The Impact of Antibiotics on the Development of Colorectal Cancer – A Review of Current Insights and Directions for Future Research - Karol Zagórski; Mateusz Kozik; Nina Skalska-Dziobek; Weronika Małagocka; Karolina Chybowska; Maria Naruszewicz; Przemysław Cetnarowski (Quality in Sport)
Introduction and purpose: Colorectal cancer (CRC) is one of the most common neoplasms in the world. In Poland, CRC has a third place in incidence. There are numerous well-established risk factors for CRC, such as a western diet, low physical activity, alcohol consumption, and cigarettes smoking. Currently, the role of the colonic microbiome and the overuse of antibiotics is also highlighted in the pathogenesis of CRC. This review aims to assess the impact of antibiotic use on CRC risk, clinical characteristics, and pathological features.